Mirror neurons : a biological genesis of relational - Ceberio, Marcelo R. (2019)
The genesis of complementarity is explained based on complex neuronal systems among which are mirror neurons. This network is much more than just a mirror because, in its interaction with other brain areas, it makes it possible to configure symmetric and asymmetric relationships. Symmetric relationships are based on incidental or intentional mimicry behaviors based on the minimum difference with respect to the displayed and perceived actions, as well as emotional contagion and empathy. Asymmetric relationships, however, are based on the inhibition of mimicry, which controls the motor responses of the sensorimotor system. We present the brain areas and circuits involved in each case. In this paper, originality is achieved by interlacing the different subsystems of neuronal action with the types of relationships that make up complementarity. It is confirmed that all relationships are complementary from a relational meta-level perspective. In addition, these conclusions are shown in the optics of systemic psychotherapy, in order to reflect on the neurobiological substratum of patients’ dysfunctional relationships, as well, on the different relational positions that the expert can strategically adopt.